Methodological Recommendations on the use of Ethnic Kyrgyz Games to Strengthen the Health of Preschool Children (5-6 Years Old) - Abdyrakhmanova Dzhiparkul, Tynalieva Bakyt, Dzhanuzakov Kanat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The article presents methodological recommendations on the use of ethnic Kyrgyz games to strengthen the health of preschool children (5-6 years old), developed on the basis of the obtained results of the study of the effectiveness of their influence on improving physical development and the physical qualities of this age category. Aim: is to develop guidelines for the use of ethnic games to strengthen the physical health of children 5-6 years old and to identify its effectiveness. Methods. At the research stage, the method of analysis of documentary sources and scientific-methodological modern literature were used. Therefore, we selected and created a database of 51 ethnic games that affect the physical qualities and development of preschool children. A classification of games is given: for physical and mental development, games for the development of fingers and breathe. Results: Methodological recommendations on the use of Kyrgyz ethnic outdoor games for the development of physical and mental qualities, as well as the improvement of breathing of preschool children, were developed for the first time, and their effectiveness was experimentally validated. The classification and characteristics of ethnic games with a description of the game unit for the development of physical, mental qualities and the breath improvement are given. The content of the game, game unit, rules, game strategy, biomechanics of movements are described in detail. It also defines the ethnic principles and ethical norms that underlie in ethnic games. Conclusion: We have designed methodological instructions and a cycle of lessons for the teacher on the use of games to improve physical qualities, muscle groups, and consciousness, the formation of social skills and creative abilities of children.